MULTIVARIATE ANALYSIS OF SOY CULTIVATED UNDER NO-TILLING SYSTEMS IN PLANT COVERS OF MILET AND SORGHUM - Góes, B. C. [UNESP]; Goes, R. J.; Cremasco, C. P. [UNESP]; Gabriel Filho, L. R.A. [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2020)
The soybean crop is the main commodity of Brazilian agribusiness, being the country considered the largest producer and exporter of the crop in the world in 2019, and it is cultivated largely in the Midwest and South regions of the country. In the last decades, crop management has been intensified under the no-tillage system, taking advantage of mulch crops as a form of nutrients for the soil and benefited by the successor crop, soybean, under which such planting system is already adopted in almost 90% of soy plantations in Brazil. In this sense, it is common to use nitrogen fertilizers, aiming at greater production of matter, invigorating the soil nutrients, available for soybean cultivation, with an increase in molybdenum via leaf, to assist in the absorption of nitrogen by the fixing cultures of nitrogen. In this way, a multivariate analysis of productivity, biometric and nutritional variables of soybean cultivated under no-tillage in vegetable coverings of millet and sorghum was carried out, with the purpose of identifying the relationship of such nutrients with the productive performance of soybean culture. To this end, it was found that certain nutrients, such as potassium and nitrogen, correlate with variables that indicate productivity.
ANÁLISE MULTIVARIADA DA SOJA CULTIVADA SOB SISTEMA PLANTIO DIRETO EM COBERTURAS VEGETAIS DE MILHETO E SORGO
Keywords: Biometric Variables; Nutritional Variables; Productivity